Study of agronomically valuable synergistic effects in binary cultures of soil streptomycetes - N. A. Bokov; R. I. Abubakirova; I. G. Shirokikh (Аграрная наука Евро-Северо-Востока, 2023)
Co-culturing of microorganisms can be an effective way to control their enzymatic activity and synthesis of secondary metabolites based on the phenomenon of synergism. The effect of co-culturing in different combinations of four local Streptomyces isolates on their cellulase activity, antiphytopathogenic and phytoregulatory effects was evaluated. Strains S. antimycoticus 8Al3 and Streptomyces sp. H 27-25 exhibited an antagonistic effect against fungi of the genus Fusarium and Alternaria. Binary cultures were composed so that the cellulolytic and antagonist strains were present. Significantly higher cellulase activity in comparison with monoculture (3800 units/10 min/g) was demonstrated by the binary association of strains S. griseoaurantiacus Mb 4-2 + S. antimycoticus 8Al3 (13215 units/10 min/g). When these isolates were co-cultured, an increase in the antifungal activity of the binary culture (18.76±6.1 mm) compared to that of its constituent S. antimycoticus 8Al3 (11.09±6.39 mm) was also noted. The mean value of the growth inhibition zones of phytopathogenic fungi (18.76±6.1 mm) was comparable with that of the reference preparation, the commercial antimycotic terbinafine (19.8±6.2 mm). Binary artificial associations in tests for phytoregulatory action, as well as monocultures of their constituent streptomycete isolates, had no significant effect on germination and morphometry of wheat seedlings. The absence of phytoinhibitory effect of the binary culture S. griseoaurantiacus Mb 4-2 + S. antimycoticus 8Al3, combined with agronomically valuable properties such as cellulase activity and antagonism to phytopathogenic fungi give grounds for its use for the development of a soil-improving biopreparation. Further study of the properties of the binary association, in particular, the possibility of its combination with PGPR-bacteria (Plant Growth-Promoting Rhizobacteria), will constitute the subject of further research.